Let s marry the knowledge of farmers and scientists - Jusi, Malcolm Sellu (Technical Centre for Agricultural and Rural Cooperation, 2000)
Low-resource farmers are quite capable of selecting appropriate plant material even in difficult environments, but they need skills and genetic diversity from both within and outside their locality. Although farmers and breeders may differ in what...